Correlative Laboratory Nano‐CT and 360° Electron Tomography of Macropore Structures in Hierarchical Zeolites. Issue 4 (7th October 2020) - Apeleo Zubiri, Benjamin; Wirth, Janis; Drobek, Dominik; Englisch, Silvan; Przybilla, Thomas; Weissenberger, Tobias; Schwieger, Wilhelm; Spiecker, Erdmann
Abstract: Hierarchical pore structures exhibit morphological features on several length scales, which govern important materials properties in catalysis, such as catalytic activity, diffusivity or selectivity. Correlative tomography offers unique opportunities for a comprehensive and scale‐bridging 3D characterization of such complex pore morphologies, which is crucial to further optimize materials design and synthesis routines. This study explores the capabilities of correlative 360° electron tomography (ET) and lab‐based nano X‐ray computed tomography (Nano‐CT) enabling 3D analyses of volumes of up to (60 µm)³ with down to nm resolution, as demonstrated for zeolite particles with embedded macropores. By first applying the two techniques to the same particle the higher resolution and fidelity of ET are used to improve the segmentation of pore space in the Nano‐CT reconstruction. Extended statistical relevance and access to interparticle pore space are obtained from reconstructions of larger particle agglomerates, using the large‐field‐of‐view mode of the Nano‐CT. The presented correlative approach enables real space analyses of important pore characteristics for comparison with complementary pore characterization techniques. Moreover, by investigating samples from different stages of the synthesis, 360°‐ET and Nano‐CT provide unique insights into the formation mechanism of porous materials, as demonstrated for the steam‐assisted crystallization of the macroporous zeolite particles. Abstract : Hierarchical pore structures exhibit morphological features on several length scales, which govern important materials properties, making scale‐bridging 3D characterization indispensable. This study demonstrates the capabilities of correlative 360° electron tomography and lab‐based nano X‐ray computed tomography allowing for 3D analyses of volumes of up to (60 µm) 3 with down to nm‐resolution applied to zeolite particles with embedded macropores.